Pure Consciousness without Ego in A. Gurwitsch’s Phenomenology - Norkus, Zenonas (Problemos, 1989)
The version of transcendental-phenomenological philosophy put forward by distinguished American phenomenologist A. Gurwitsch (1901-1913) is analyzed. Most consideration is given to his conception of intentionality, which is said to synthesize the idea of gestaltpsychology and Husserlian phenomenology. It is shown that A. Gurwitsch’s concept of intentionality differs from the Husserlian one: the first treating an intentional act as a two-place relation, while the latter – as a four-place relation.